Antithrombotic therapy after mitral valve repair: VKA or aspirin? - van der Wall, Sake J. (J Thromb Thrombolysis, 2018)
The optimal antithrombotic therapy following mitral valve repair (MVr) is still a matter of debate. Therefore, we evaluated the rate of thromboembolic and bleeding complications of two antithrombotic prevention strategies: vitamin K antagonists (VKA) versus aspirin. Consecutive patients who underwent MVr between 2004 and 2016 at three Dutch hospitals were evaluated for thromboembolic and bleeding complications during three postoperative months. The primary endpoint was the combined incidence of thromboembolic and bleeding complications to determine the net clinical benefit of VKA strategy as compared with aspirin. Secondary objectives were to evaluate both thromboembolic and bleeding rates separately and to identify predictors for both complications. A total of 469 patients were analyzed, of whom 325 patients (69%) in the VKA group and 144 patients (31%) in the aspirin group. Three months postoperatively, the cumulative incidence of the combined end point of the study was 9.2% (95%CI 6.1–12) in the VKA group and 11% (95%CI 6.0–17) in the aspirin group [adjusted hazard ratio (HR) 1.6, 95%CI 0.83–3.1]. Moreover, no significant differences were observed in thromboembolic rates (adjusted HR 0.82, 95%CI 0.16–4.2) as well as in major bleeding rates (adjusted HR 1.89, 95%CI 0.90–3.9). VKA and aspirin therapy showed a similar event rate of 10% during 3 months after MVr in patients without prior history of AF. In both treatment groups thromboembolic event rate was low and major bleeding rates were comparable. Future prospective, randomized trials are warranted to corroborate our findings.